CAN TREASURY BILLS ISSUED INFLUENCE ECONOMIC GROWTH IN NIGERIA? AN EMPIRICAL ANSWER - Vincent Afure Akpotor & Edoseghe Jeffery Egharevba (Advance Scholars Publication Published by International Institute of Advance Scholars Development https://aspjournals.org/Journals/index.php/bijaefa, 2022)
ABSTRACT: Money market is a component of the financial system, which is for trading in short-term financial instruments. The major objective of this study is to analyze the effect Treasury bills issue on economic growth in Nigeria from 1986-2019. The independent variables employed in the study include Treasury Bills (TB), Treasury bill Rate (TBR), Inflation Rate, (INFR) and Money Supply (MS), Growth Rate of Gross Domestic Product (RGDP) was used to proxy economic growth. Data were obtained from Central Bank of Nigeria Statistical Bulletin 2019, and analyzed using Vector Error Correction Model (VECM) Regression techniques. The findings revealed that Treasury bills have insignificant negative effects on economic growth in Nigeria. It was recommended that, issuance of Treasury bills should not just be to address inflationary and deflationary shocks. But, should also be tailored towards enhancing investment potentials in the economy. This can be done by supervising the subscription procedure or by assigning certain quota to individuals and corporate investors that are not commercial banks.
Money Market
Keywords: Money market; Treasury Bills; Inflation Rate; Money Supply